Frozen "buko" puree as beverage base - Pongos, Maria Angela Catalya; Gomez, Maria Theresa L. (1991.)
The study was aimed at determining the acceptability of the frozen "buko" puree as beverage base. The most suitable "buko" stage of maturity for the utilization as raw material in the preparation of frozen "buko" puree was determined. Among three stages, the "malakanin" stage of maturity was found to be the most suitable. This generalization was based on the results of the objective tests undertaken in the first phase. The desired frozen "buko" puree was found to be with the 1.0:1.5 "buko" meat to develop using the Qualitative Descriptive Analysis technique. QDA results were statistically analyzed using the ANOVA which showed that quality attributes remained unaltered even though stored young coconuts for nine days were used. Standardization of procedure, product costing and product performance were likewise done.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coconut products